Antithrombotic therapy for long-term secondary prevention of acute coronary syndrome in high-risk patients - Husted S (Therapeutics and Clinical Risk Management, 2015)
Steen Husted1,2 1Department of Biomedicine, Centre for Clinical Pharmacology, Aarhus, 2Department of Medicine, Hospital Unit West, Herning, Denmark Abstract: Patients with acute coronary syndrome (ACS) represent a major clinical burden, because they tend to experience recurrent ischemic events. Acute management of patients with ACS includes combination antithrombotic therapy composed of a parenteral anticoagulant and dual-antiplatelet therapy. Dual-antiplatelet therapy is also recommended for long-term secondary prevention of ACS. Despite advances in the antithrombotic therapies available, clinical trials suggest that patients with ACS still face a ~10% risk of another event within 12–15 months of the index event. Certain patient populations, such as elderly patients and those with renal impairment or heart failure, are at higher risk of recurrent ACS events, because these patients have more vascular ischemic and bleeding risk factors than most other patients. Evidence from the GRACE and CRUSADE registries suggests underuse of the guideline-recommended evidence-based therapies for the management of ACS in such patients. This review summarizes the current standard of care for patients with ACS, focusing on long-term secondary antithrombotic strategies. Registry data are used to identify high-risk patient populations; the recent antiplatelet and anticoagulant Phase III trial data are summarized to highlight any patient populations who receive greater or lesser benefit from specific long-term antithrombotic strategies. Guideline recommendations are discussed and suggestions are provided to help improve implementation of long-term secondary prevention strategies and patient prognosis after an ACS event. Keywords: acute coronary syndrome, anticoagulants, antiplatelets, risk assessment, secondary prevention